The Implementation of Regional Regulation of Kupang City Number 7 of 2000 Concerning Green Open Space in The Environmental Development of Kupang City - Bartholomeus Mbe Se; Jimmy Pello; Saryono Johanes (Faculty of Law, Universitas Jenderal Soedirman, 2019)
One of the important aspects in environmental development is the use of green open space that serves its objectives and functions. Therefore, the Kupang City Regulation Number 7 of 2000 as a legal guarantee in the use of green open space was issued. The legal issue being studied is whether the implementation the Kupang City regional regulation Number 7 of 2000 is in line with the purpose and function. The research is an empirical research. The results of the study found that implementation of Kupang City Regulation Number 7 of 2000 has not served its purpose and function. It was caused by various factors, as law enforcement officials factor and inadequate supporting facilities and infrastructure. Therefore, it was recommended that there should be seriousness in preparing both supporting facilities and infrastructure for the implementation of these local regulations. Keywords: The Implementation Of There Is A Regional Regulation; The Construction Of The Environment; Green Open Space